2016
DOI: 10.1108/ribs-01-2014-0013
|View full text |Cite
|
Sign up to set email alerts
|

Psychological contracts and intention to leave with mediation effect of organizational commitment and employee satisfaction at times of recession

Abstract: Purpose The purpose of this paper is to understand the implications of psychological contract on employees’ intention to leave and their relationship with employee commitment and satisfaction. The study focuses on measuring these attributes in the United Arab Emirates’ (UAE) multicultural workforce. Design/methodology/approach Data were collected from a total of 373 employees from government, semi-government and private organizations covering different hierarchical levels across various industries. Structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 68 publications
2
34
0
4
Order By: Relevance
“…Other studies have also reported a negative relationship between employees' organizational commitment and the intention to quit [6], [8], [56]. Several other studies which investigated the effect of organizational commitment on the intention to quit, reported that organizational commitment is the behavioral indicator of employee's discharge from the company [14], [26].…”
Section: Organizational Commitment and Intention To Quitmentioning
confidence: 98%
See 2 more Smart Citations
“…Other studies have also reported a negative relationship between employees' organizational commitment and the intention to quit [6], [8], [56]. Several other studies which investigated the effect of organizational commitment on the intention to quit, reported that organizational commitment is the behavioral indicator of employee's discharge from the company [14], [26].…”
Section: Organizational Commitment and Intention To Quitmentioning
confidence: 98%
“…Several other studies which investigated the effect of organizational commitment on the intention to quit, reported that organizational commitment is the behavioral indicator of employee's discharge from the company [14], [26]. Some other empirical evidence also reported that organizational commitment has a significant effect on intention to quit [6], [8], [13], [30], [31, [32], [51], [59].…”
Section: Organizational Commitment and Intention To Quitmentioning
confidence: 99%
See 1 more Smart Citation
“…Contemporary approaches to the nature of the psychological contract introduce the idea of contract breach or violation as the main mechanism that links the psychological contract to organisational and individual performance. The existing reflection also implies that a breach of contract will generate more intense reactions than unfulfilled expectations, as it triggers anger, a sense of betrayal, and reluctance, which can dampen motivation, undermine job satisfaction and lead to a desire to leave the organisation (Turnley et al 2003;Behery et al 2016).…”
Section: Makin Cooper Cox (2000: 33)mentioning
confidence: 99%
“…The authors made a proposition that individual, organizational, and environmental factors affect the turnover intention. Behery [36]investigated the effect of relational psychological contract on turnover intention mediated by satisfaction and organizational commitment in UAE's private and public organizations.…”
Section: Leadership Style and Turnover Intention: The Moderating Rolementioning
confidence: 99%